ShadeMotion: the analysis of tree shade patterns tutorial - Somarriba, Eduardo; Zamora, Randall; Barrantes, José; Malek, Matthias; Vargas, Eduardo; Sinclair, Fergus L.; Quesada, Francisco (2021)
ShadeMotion 5.1.41 is a software application that calculates the number of hours of shade accumulated on each point (grid cell) on a plot due to the presence of trees, in any number, sizes and crown shapes and in any location on Earth. The analysis of shade patterns is central to the design and management of trees in the agricultural landscape.